The Cost of Emotions in the Workplace : Bottom Line Value of Emotional Continuity Management - Hawkins Mitchell, Vali, 1949- (Rothstein catalog on disaster recovery., 2013)
Shows how to systematically manage your organizational emotional culture. Introduces Emotional Continuity Management and provides tested system to observe, predict, prepare, and write policy to prevent employee problems. Offers tools to quantify costs of disruptive emotional incidents, from bad managers, office bullies to workplace violence.